The European Medicines Agency Review of Decitabine (Dacogen) for the Treatment of Adult Patients With Acute Myeloid Leukemia: Summary of the Scientific Assessment of the Committee for Medicinal Products for Human Use. (18th April 2016) - Nieto, Maria; Demolis, Pierre; Béhanzin, Eliane; Moreau, Alexandre; Hudson, Ian; Flores, Beatriz; Stemplewski, Henry; Salmonson, Tomas; Gisselbrecht, Christian; Bowen, David; Pignatti, Francesco
Abstract: On September 20, 2012, a marketing authorization valid throughout the European Union (EU) was issued for decitabine for the treatment of adult patients aged 65 years and older with newly diagnosed de novo or secondary acute myeloid leukemia (AML) who are not candidates for standard induction chemotherapy. Decitabine is a pyrimidine analog incorporated into DNA, where it irreversibly inhibits DNA methyltransferases through covalent adduct formation with the enzyme. The use of decitabine was studied in an open-label, randomized, multicenter phase III study (DACO-016) in patients with newly diagnosed de novo or secondary AML. Decitabine ( n = 242) was compared with patient's choice with physician's advice ( n = 243) of low-dose cytarabine or supportive care alone. The primary endpoint of the study was overall survival. The median overall survival in the intent-to-treat (ITT) population was 7.7 months among patients treated with decitabine compared with 5.0 months for those in the control arm (hazard ratio [HR], 0.85; 95% confidence interval [CI], 0.69–1.04; p = .1079). Mature survival data after an additional year of follow-up were consistent with these results, with a median overall survival of 7.7 months in patients treated with decitabine and 5.0 months in the control arm (HR, 0.82; 95% CI, 0.68–0.99; p = .0373). Secondary endpoints, including response rates, progression-free survival, and event-free survival, were increased in favor of decitabine when compared with control treatment. The most common adverse drug reactions reported during treatment with decitabine are pyrexia, anemia, thrombocytopenia, febrile neutropenia, neutropenia, nausea, and diarrhea. This paper summarizes the scientific review of the application leading to approval of decitabine in the EU. The detailed scientific assessment report and product information (including the summary of product characteristics) for this product are available on the EMA website (http://www.ema.europa.eu ). Abstract : This review focuses on the European Medicines Agency approval for decitabine, a hypomethylating agent for the treatment of adult patients age 65 years and older with newly diagnosed de novo or secondary AML who are not candidates for standard induction chemotherapy.